2011
DOI: 10.1002/biot.201000446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating 13C enrichment data of free amino acids for precise metabolic flux analysis

Abstract: Metabolic flux analysis using (13)C enrichment data of intracellular free amino acids (FAAs) can improve the time resolution of flux estimation compared to analysis of proteinogenic amino acid data owing to the faster turnover times of FAAs. The nature of the (13)C enrichment dynamics of FAAs remains obscure, however, especially with regard to its dependence on culture conditions, even though an understanding of dynamic behavior is important for precise metabolic flux estimation. In this study, we analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…While a significant amount of pyruvate (Pyr) and acetyl-CoA (AcCoA) are secreted to the medium as formate and acetate, the remaining carbon flows into the TCA cycle. The flux distribution is essentially comparable to a previously reported result [17]. In this study, 95% confidence intervals of each flux were estimated by the grid search method (represented as error bars in Figure 3).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…While a significant amount of pyruvate (Pyr) and acetyl-CoA (AcCoA) are secreted to the medium as formate and acetate, the remaining carbon flows into the TCA cycle. The flux distribution is essentially comparable to a previously reported result [17]. In this study, 95% confidence intervals of each flux were estimated by the grid search method (represented as error bars in Figure 3).…”
Section: Resultssupporting
confidence: 90%
“…An investigation of the continuous culture of E. coli using a simplified metabolic model demonstrated that PAAs- and FAAs-based MFA methods can produce compatible flux distributions [17]. The MFA performed in this study using the generally accepted metabolic model confirmed that essentially identical flux distributions are estimated from the 13 C enrichment data of PAAs (PAAs_fullset) and FAAs (FAAs_fullset), with the 95% confidence intervals of the two sets overlapping each other (Figure 2 and Figure 3).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In that work, the antibiotic tolerance of ten evolved clones was verified by conventional methods and were therefore selected for the present study along with the parental strain (Table 1). Frozen pure bacterial stocks (−80 °C) were cultured in 10 mL modified M9 medium 24 in test tubes placed in water bath shakers with 150 strokes/min shaking (Personal-11, Taitec Co., Saitama, Japan). Cells were transferred to 96-well microplates (3595, Corning Inc., NY, USA) and cultured in modified M9 medium using an automated culture system 25 which consists of a Biomek® NX span8 laboratory automated workstation (Beckman Coulter, Tokyo, Japan) in a clean booth connected to a microplate reader, a shaker incubator (STX44; Liconic, Mauren, LI), and a microplate hotel (LPX220, Liconic, Mauren, LI).…”
Section: Methodsmentioning
confidence: 99%
“…For GC-MS, the hydrolysate was mixed with an equal volume of N-(tert-butyldimethylsilyl)-N-methyl-trifluoroacetamide (MTBSTFA), and the mixture was incubated at 105 C for 1 h. Next, 1 mL of the sample was injected into the GC-MS system (7890A GC and 5975C GC/MSD, Agilent Technologies, Santa Clara, CA, USA), according to a previously described method (6,7). The GC-MS data were corrected considering the natural abundance of C, H, N, O, and Si isotopes for 13 C-MFA (8).…”
Section: Gc-ms Analysis Of Proteinogenic Amino Acidsmentioning
confidence: 99%